Mechanical Rat Repellant Device Powered by STEAM Based Water Turbine - Ngazizah, Nur; Adilah, Nur (Education, Science, and Technology International Conference, 2024)
Rats are one of the rodent pests of rice plants. Plant damage is characterized by a pattern of rice plant death from the middle of the rice field to the edge of the rice field. Rat eradication, including traps and rat poison, actually causes damage to the rice field ecosystem. This research aims to produce and test a rat repellent device that produces mechanical sound powered by a water turbine by using items that are around. The research method used is the Research and Development (R&D) based on Science, Technology, Engineering, Art, and Mathematics (STEAM). Research by Manohar et al. (2019) stated that after mice were placed in a box equipped with noise of 60 dB-90 dB, the mice left the box to avoid the noise because it was considered to arouse fear and be disturbing. The results of this research are in the form of: 1) The means for expelling mice is a mechanical mouse repellent device powered by a water turbine. 2) The feasibility of a Water Turbine Powered Mechanical Rat Repellent Device is based on the STEAM aspect, namely the science aspect of using water flow to drive a turbine; the technological aspect uses the basic principles of propeller motion on a turbine; engineering aspects of using digital media as a means to create product designs; the art aspect uses idiophones sounds produced from cans; The mathematical aspect uses the basic formula for spindle rotation. Based on research results, a STEAM-based water turbine powered mechanical rat repellent device was declared suitable for use.